Impact of Smart Irrigation Systems on Water Resource Sustainability in India - Nureen, Puteri (Journal of Environment, 2024)
Purpose: The purpose of this article was to examine impact of smart irrigation systems on water resource sustainability Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that Smart irrigation systems enhance water sustainability by improving water use efficiency, reducing wastage, and supporting aquifer recharge. Technologies like soil moisture sensors, weather-based controllers, and precision irrigation reduce water consumption by up to 30% while boosting crop yields. In developed economies, adoption has led to significant groundwater conservation, while challenges like cost and accessibility hinder widespread use in developing regions. Despite these barriers, smart irrigation offers long-term benefits, including improved water availability, climate resilience, and reduced environmental stress, making it vital for sustainable water management. Unique Contribution to Theory, Practice and Policy: Diffusion of innovations theory, socio-ecological systems framework & sustainability transitions theory may be used to anchor future studies on the impact of smart irrigation systems on water resource sustainability. Training initiatives and demonstration sites will familiarize end-users with interpreting sensor data, adjusting irrigation schedules, and maintaining equipment. Regulatory frameworks can mandate the integration of precision irrigation technologies into new agricultural developments and reward compliance through certification schemes.